Management of pedagogical directive leadership and its relationship with teaching performance at the secondary level of the educational institution "francisco vidal laos". Supe - canyon. Lima 2018 - Sánchez Regalado, Jacqueline Lisset (2019)
There is precariousness in the responsibilities of the director of an educational institution, because to his administrative function, today there is a clear disposition to promote pedagogical directive leadership. Therefore, research is consolidated so that instead of assuming a transectional dimension, rather its function must be transformative, so that they are modified, altering the conditions of the school and the classroom to improve not only the teaching performance, but also the level and quality of student learning. Establishing a vision, direction, expectations and goals is paramount in the pedagogical aspects, to improve the redesign and organization to promote pedagogical management leadership and to program management with quality teaching programs according to each region. reason for this investigation. The results allow us to conclude that there is a relationship between the management of pedagogical directive leadership and the teaching performance in the educational institution "Francisco Vidal Laos". Supe - Barranca. Lima 2018, since it was proved that the value of p being less than 0.05. and have a correlation coefficient, r = 0, 768 which represents a correlation of 76.8%. This significance is found through Spearman's Rho statistical test. It is shown that the institutional planning is related to the teaching performance, since it was found that the correlation coefficient, r = 0, 543 which represents a correlation of 54.3%. Likewise, the management of human, material, time, financial and risk prevention resources is related to the teaching performance, whose correlation coefficient, r = 0, 563 represents a correlation of 56.3%. The evaluation and the rendering of accounts are related to the teaching performance whose coefficient is r = 0, 638 which represents a correlation of 63.8%. The management of the pedagogical processes are related to the teaching performance, its correlation coefficient is r = 0,593 which represents a correlation of 59,3%. We note that there are indeed significant correlations between pedagogical management leadership and teaching performance between each of the sub dimensions studied.